2009
DOI: 10.1111/j.1529-8817.2009.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

TAXONOMIC REEXAMINATION OF CHARA GLOBULARIS (CHARALES, CHAROPHYCEAE) FROM JAPAN BASED ON OOSPORE MORPHOLOGY AND rbcL GENE SEQUENCES, AND THE DESCRIPTION OF C. LEPTOSPORA SP. NOV.1

Abstract: Chara globularis Thuillier (=f. globularis sensu R. D. Wood) is a widespread species of the genus and inhabits fresh- and brackish-water environments. In an attempt to reexamine the taxonomic status of C. globularis collected from Japan, we reassessed vegetative and oospore morphology of Japanese material and herbarium specimens originating from Europe (including the type specimen) and conducted molecular phylogenetic analyses based on rbcL gene sequences. Although the other vegetative morphologies were consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 25 publications
1
25
0
4
Order By: Relevance
“…The quality and quantity of the DNA were determined using a fluorometer (Eppendorf, Hamburg, Germany), but the integrity of the extracted DNA was estimated on 1% TBE-agarose gel. The PCR amplification and sequencing of the atpB gene were accomplished using the primers described by Sakayama et al (2004), while that of the rbcL and matK made use of primers described by Sakayama et al (2009) andsanders et al (2003), respectively. Analyses were performed in a Veriti gradient Thermal Cycler (Applied Carlsbad, CA, USA Each 20 μl reaction contained 10 mM each of dATP, dCTP, dGTP, and dTTP; 0.5 μM of each primer, 4.0 μl 5´ reaction buffer, 0.2 μl Phusion Hot Start II HF DNA Polymerase (Thermo Scientific, Waltham, MA, USA.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality and quantity of the DNA were determined using a fluorometer (Eppendorf, Hamburg, Germany), but the integrity of the extracted DNA was estimated on 1% TBE-agarose gel. The PCR amplification and sequencing of the atpB gene were accomplished using the primers described by Sakayama et al (2004), while that of the rbcL and matK made use of primers described by Sakayama et al (2009) andsanders et al (2003), respectively. Analyses were performed in a Veriti gradient Thermal Cycler (Applied Carlsbad, CA, USA Each 20 μl reaction contained 10 mM each of dATP, dCTP, dGTP, and dTTP; 0.5 μM of each primer, 4.0 μl 5´ reaction buffer, 0.2 μl Phusion Hot Start II HF DNA Polymerase (Thermo Scientific, Waltham, MA, USA.)…”
Section: Methodsmentioning
confidence: 99%
“…12). Representatives of genera Nitellopsis, Nitella, Lychothamnus and Tolypella were selected as an outgroup according to previous study (mCCoUrT et al 1996(mCCoUrT et al , 1999karol et al 2001;sakayama et al 2002sanders et al 2003 andSakayama et al 2009). The rbcL DNA sequences analysed in this study were 1,244 bp (excluding gaps) and correspond to position 5 -1,249 of the Chara vulgaris rbcL gene (TUrmel et al 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed statistical analyses of oospore dimensions have also been studied by mandaL et al (2002) and Urbaniak (2009). Sakayama et al (2009Sakayama et al ( , 2015 and Perez et al 2014) showed that the combination of different types of data (SEM oospore morphology and molecular data) can be more informative than when taken separately, and can be used for taxonomic distinction, especially in closely related species of the genus Nitella or Tolypella.…”
Section: Introductionmentioning
confidence: 99%
“…For the genus Chara, molecular phylogenetic analyses, based on chloroplast and nuclear DNA gene sequences, together with analyses of morphological characteristics, have also been carried out to resolve the relationships at species or genic level (mccoUrt et al 1996;meierS et al 1999;SanderS et al 2003;Sakayama et al 2009;Schneider et al 2015;noWak et al 2016). By contrast, in the same way using combined morphological characteristics of the species and analysis of about 6214 bp, noWak et al (2016) coudl not separate Chara individuals and all of the studied species.…”
Section: Introductionmentioning
confidence: 99%